Pemodelan Simulasi untuk Mengurangi Antrian pada Fasilitas Layanan Kesehatan - Bahariandi Aji Prasetyo; Tarigan, Elsya Paskaria Loyda; Sri Zetli (Fakultas Teknik UMRI, 2023)
Service is the main indicator of the sustainability of a service. The quality of services is the main factor that must be considered in maintaining the existence and competition of services, including health facility services. This research was conducted at one of the health service providers in the city of Batam. One aspect of health service quality is queuing service. Therefore, the quality of service in the queuing system in health facilities is an interesting thing to research. This research measures the level of optimality of the queuing system currently in effect at the Saffira Mitra Medika clinic. The measurement focuses on service time, the number of patients served, and the waiting time for patients to be served in the queue system. The results of measuring the current queuing system are compared with other proposed queuing system scenarios, so that the level of patient satisfaction as customers is met. The proposed queuing system was obtained through a simulation approach, with the help of Flexsim software. A simulation approach was chosen to facilitate modeling in the proposed queuing system